CIDHAL: Case Study of a Feminist Organization - Susan J. Bracken (Adult Education Research Conference, 2002)
CIDHAL, a feminist community education organization, located in Southern Mexico, has been a critical participant in the feminist, labor, and urban popular movements in Mexico and Latin America. By exploring an overview of its history and social context, adult educators are left with important questions and reflections about the issues this type of organization experiences.